2000
DOI: 10.1046/j.1523-1747.2000.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical Treatment with Liposomes Containing T4 Endonuclease V Protects Human Skin In Vivo from Ultraviolet-Induced Upregulation of Interleukin-10 and Tumor Necrosis Factor-α

Abstract: Exposing human skin to ultraviolet radiation causes DNA damage, sunburn, immune alterations, and eventually, skin cancer. We wished to determine whether liposomes containing a DNA repair enzyme could prevent any of the acute effects of irradiation when applied after ultraviolet exposure. Fifteen human patients with a prior history of skin cancer were exposed to two minimal erythema doses of ultraviolet radiation on their buttock skin. Liposomes containing T4 endonuclease V or heat-inactivated enzyme were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(93 citation statements)
references
References 56 publications
4
86
0
1
Order By: Relevance
“…For example, UV impairs APC function (37), it induces the release of immunosuppressive cytokines like IL-10 (38), and it drives T lymphocytes into apoptotic cell death (39). Many of the immunosuppressive effects are much more weakly pronounced when UV-induced DNA lesions are reduced, e.g., by acceleration of DNA repair (40,41). Therefore, UV-induced DNA damage has been recognized as the major, but not the only mediator of the immunosuppressive effects of UVR.…”
Section: Discussionmentioning
confidence: 99%
“…For example, UV impairs APC function (37), it induces the release of immunosuppressive cytokines like IL-10 (38), and it drives T lymphocytes into apoptotic cell death (39). Many of the immunosuppressive effects are much more weakly pronounced when UV-induced DNA lesions are reduced, e.g., by acceleration of DNA repair (40,41). Therefore, UV-induced DNA damage has been recognized as the major, but not the only mediator of the immunosuppressive effects of UVR.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, based on human action spectroscopy in vivo, our data strongly suggest that DNA, specifically in the basal layer, is an important chromophore for TNF␣ and supports the in vitro mouse kera- tinocyte studies of Kibitel et al (11), in which T4 endonuclease V (T4N5)-enhanced CPD repair was shown to reduce TNF␣ protein production. A similar in vivo approach was made by Wolf et al (24). However, these authors were not able to demonstrate any significant reduction of epidermal CPD by T4N5 or the presence of TNF␣ protein, although the T4N5 did reduce mRNA levels.…”
Section: Discussionmentioning
confidence: 77%
“…it was already demonstrated that application of t4 endoV on irradiated skin effectively prevents the up-regulation of interleukin-10 and TNF-alpha, therefore significantly lowering the risk for skin neoplastic growth (7).…”
Section: Resultsmentioning
confidence: 99%